Perceived Communication and Psychological Factors by Shopkeepers Regarding Goods and Services Tax (GST) - Semwal, Shatakshi; Rani, Ella; Verma, Vandana; Malik, Joginder Singh (Indian Journal of Extension Education, 2021)
India has gone through a lot of changes during past years and this scenario had an adverse impact on Indiaâ€™sÂ economy. First there was demonetization to choke back the black money and later there was Goods and Services Tax (GST) that is still updating its tax slabs. Due to the implementation of GST, both consumers and shopkeepersÂ finds themselves with low knowledge level and negative perception of GST. So, there arises the need to find theÂ factors affecting the people in accepting and rejecting this new tax reform. The present study was conducted in Hisar city of Haryana state where 30 respondents from five respective sections were selected i.e. Food, Clothing and Textiles, Electrical appliances, Medical and Cosmetics and Communication and Transportation; thus makingÂ a total sample of 150 respondents. Data inferred that majority of the respondents had accessibility to newspapers, televisions and mobile phones to receive and share information. Further, they used to obtain information regarding GST from their friends and the shopkeepersâ€™ meetings held in their area; processing and its evaluationÂ was done by discussing it with elders and other shopkeepers; and dissemination of information was done through the group meetings and newspaper articles/social media posts respectively. It was also found that they had high change proneness with medium risk orientation and entrepreneurial motivation. The present study may attracts the attention towards giving the shopkeepers and consumers efficient and effective news aboutÂ various household products and holding training for paying their personal taxes.